2021
DOI: 10.3389/fonc.2021.774979
|View full text |Cite
|
Sign up to set email alerts
|

CircITCH: A Circular RNA With Eminent Roles in the Carcinogenesis

Abstract: Circular RNAs (circRNAs) are a group of long non-coding RNAs with enclosed structure generated by back-splicing events. Numerous members of these transcripts have been shown to affect carcinogenesis. Circular RNA itchy E3 ubiquitin protein ligase (circITCH) is a circRNA created from back splicing events in ITCH gene, a protein coding gene on 20q11.22 region. ITCH has a role as a catalyzer for ubiquitination through both proteolytic and non-proteolytic routes. CircITCH is involved in the pathetiology of cancers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 39 publications
(43 reference statements)
1
6
0
Order By: Relevance
“…MiRNA, as a part of the ceRNA network, causes polyadenylation by binding with target sites in the 3'-UTR of mRNA, lowering mRNA stability and interfering with translation to adversely control gene expression (Nawaz et al, 2016). CircRNAs may have biological impacts on tumors by sponging target miRNAs and limiting their function, according to previous studies (Li Y. et al, 2020;Ghafouri-Fard et al, 2021;Su et al, 2022). There is no exception for circ-ITCH.…”
Section: Regulation Mechanism and Role Of Circ-itch In Tumor Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…MiRNA, as a part of the ceRNA network, causes polyadenylation by binding with target sites in the 3'-UTR of mRNA, lowering mRNA stability and interfering with translation to adversely control gene expression (Nawaz et al, 2016). CircRNAs may have biological impacts on tumors by sponging target miRNAs and limiting their function, according to previous studies (Li Y. et al, 2020;Ghafouri-Fard et al, 2021;Su et al, 2022). There is no exception for circ-ITCH.…”
Section: Regulation Mechanism and Role Of Circ-itch In Tumor Diseasesmentioning
confidence: 99%
“…Combining the database (Circular RNA Interactome and circBase) and related literature search, we considered it derived from exons 6-13 (Figure 1), while 7-14 was a writing error in correlative papers. Recently, studies have revealed that circ-ITCH is down-regulated in multiple tumor tissues, and regulates cell proliferation, migration, invasion and apoptosis of malignant tumor, indicating it might be an important tumor suppressor (Li Y. et al, 2020;Ghafouri-Fard et al, 2021;Su et al, 2022). Additionally, the down-regulation can also be seen in the peripheral blood and exosomes of patients.…”
Section: Introductionmentioning
confidence: 99%
“…MiR‐214 was also shown to be reduced by the lncRNA, MEG3 (J. Zhang et al, 2017). MiR‐214 and miR‐199a act as sponges for circular RNA‐ITCH; circular RNA‐ITCH is involved in the PTEN/PI3K/AKT and Wnt/β‐catenin pathways implicated in NAFLD fibrosis (El‐Derany & El‐Demerdash, 2020; Ghafouri‐Fard et al, 2021; Riaz et al, 2021).…”
Section: Exosomal Mirnas Involved In Fibrosis Of Nalfd As a Biomarkermentioning
confidence: 99%
“…Therefore, the sponging of target miRNAs by circITCH regulates ITCH levels. The presence of circITCH in cells leads to an increase in ITCH mRNA levels resulting in greater ITCH ubiquitin activity, which decreases the activity of oncogenic factors [ 129 ]. In CRC, the expression of circITCH was downregulated in cancerous cells, resulting in low levels of ITCH gene expression.…”
Section: Circular Rnasmentioning
confidence: 99%